13.1k views
0 votes
Solve for x
-4(-x -1) + 2x + 3 = 43​

User Mindoftea
by
5.1k points

1 Answer

3 votes

Answer:

x=36

Explanation:

-4(-x-1)+2x+3=43

or, 4x+4+2x+3=43( when there is - sign in multiply the sign will be +)

or, 4x+2x+4+3=43( arranging the like terms)

or, 6x+7=43( adding both numbers)

or, 6x=43-7(when there is + sign in one side if it will go to another side it will be -sign)

or, 6x=36(substracting the numbers)

or, x=36/6(when there is multiply in one side there will be divide)

or, x=6

Hope it is helpful for you

User Meolic
by
5.5k points